(Un)happy transition? Subjective Well-being in European Countries in 1991-2008 and Beyond - Jirí Vecerník; Martina Mysíková (Austrian Institute of Economic Research (WIFO), 2014)
This paper contributes to the debate about the impact of the transition to subjective well-being. After reviewing the relevant literature the authors draw on the surveys of the European Values Study between 1991 and 2008 to describe the trends in life satisfaction in 13 "Western" and 11 "Eastern" countries. The analysis finds that life satisfaction levels in transition countries have come to approach those in the West: the "rather unhappy" 1990s were followed by the "rather happy" 2000s. The correlation between life satisfaction and GDP reflects this process of convergence: the two separate lines in 1991 merge to become a single continuum later on. The characteristics of respondents are however more important than GDP, and a regression of life satisfactions with basic demographic and stratification variables shows their reinforcing effect in both Eastern and Western countries. As a result, the explained variance of life satisfaction was increasing. The findings of other surveys reporting on developments of attitudes since 2008 vary but are far from proving a uniform negative impact of economic recession on life satisfaction. The paper concludes by suggesting that various surveys have to be compared in order to obtain more reliable information on the development and factors of subjective well-being.
Keywords: 330; Strukturwandel; Sozialer Wandel; Gesundheit; Zufriedenheit; Soziale Lage; Europa